Utilisasi Proses Produksi Kemasan Kantong Untuk Kebutuhan Koperasi di Pesantren Uzlifatil Jannah, Tangerang, Banten - -, Zulkarnain; -, Muryeti; Silvia, Deli; Imam, Saeful; Prastiwinarti, Wiwi; Yamin, Iqbal (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2024)
The Uzlifatil Jannah Islamic Boarding School Cooperative was founded to provide practical learning experiences for students in terms of business management and business development. However, the cooperative business does not yet have an identity (branding) on its shopping bag packaging and does not have the knowledge and skills to produce bag packaging. This service activity aims to share knowledge and skills in the production of bag packaging (totebags) so that it becomes an effective branding medium for Islamic boarding school cooperatives. The methods used are observation and interviews, material lectures, and training. Participants in this activity are students and Islamic boarding school managers. Material and training (practice) were in accordance with participants' needs to increase knowledge and skills in the tote bag production process. The implementation of this service activity has succeeded in becoming an inspiration for the Islamic Boarding School to continue developing its cooperative business.